Optimization of Pricing Strategies to Enhance Purchase Decisions for Internet Packages in Medan Community - Ema Saswita Cania; Abdul Mulia Hasibuan; Aisya Trixsi Pramaisela; Saparuddin Siregar (Universitas Islam Negeri Sumatera Utara, 2023)
Indonesia, as a developing country with a large population, has a highly potential market in the telecommunications sector, particularly for internet packages. Telkomsel, one of the largest providers in Indonesia, faces challenges in addressing the perception of higher prices compared to its competitors. This study aims to evaluate Telkomsel's pricing strategy and its impact on consumer purchasing decisions, focusing on the Medan area, which has seen rapid growth in internet usage. The methods used in this research include Deep Interviews to understand why consumers choose Telkomsel despite its higher prices, and Training for Telkomsel's management team on setting more competitive prices without sacrificing quality. The results from the training show that Telkomsel's management team has begun implementing pricing strategies that better align with consumers' purchasing power, emphasizing service quality as an added value. The discussion of results indicates that although Telkomsel's internet package prices are considered high, consumers still choose Telkomsel due to its superior service quality, including extensive network coverage, fast and stable signals, and the ability to reach remote areas. Effective communication strategies about these advantages and customer loyalty programs have proven to increase customer satisfaction and loyalty.